Critical care assistants opinions of the Health Professions Council of South Africa register closure and change in clinical practice guidelines - Rosslee, Frauke Renate (My University, 2020)
Critical Care Assistants (CCAs) have traditionally provided advanced life support care to patients in the prehospital field in South Africa. Training of CCAs came to an end in 2018 and their register was closed at the Health Professions Council of South Africa (HPCSA). At the same time, the HPCSA Professional Board for Emergency Care (PBEC) implemented Clinical Practice Guidelines (CPGs) for the emergency care profession. This resulted in a change in the scope of practice for CCAs. This qualitative study explored the opinions of CCAs on the HPCSA register closure and change in CPGs. Fourteen CCAs were interviewed from South Africa’s Gauteng Province. Data were collected through individual in-depth interviews, which were transcribed and analysed to derive themes and categories. Three themes were identified. These were education opportunities, personal impact and concern for profession. Pathways for CCAs to access Higher Education Emergency Care programmes need to be established. Communication platforms need to be developed for the effective implementation of the CPGs.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Health Science in Education to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020
Keywords: Critical care; Nursing care